Association between health status and sociodemographic, clinical and treatment disparities in the Patient-centered Outcomes Related to TReatment Practices in Peripheral Arterial Disease: Investigating Trajectories (PORTRAIT) registry. (February 2018) - Noyes, Adam M; Abbott, J Dawn; Gosch, Kensey; Smolderen, Kim; Spertus, John A; Hyder, Omar; Soukas, Peter; Shishehbor, Mehdi H; Aronow, Herbert D
Patients with peripheral artery disease (PAD) and intermittent claudication (IC) have impaired functional status and quality of life. However, little is known about which factors are associated with poorer health status at the time of initial presentation for PAD specialty care. Characterization of such features might provide insight into disparities that impact health status in this population. A total of 1258 patients from the United States, the Netherlands and Australia with new or worsened IC were enrolled at their first PAD specialty care visit between June 2011 and December 2015. The mean Peripheral Artery Questionnaire (PAQ) Summary Score (range 0–100), a disease-specific health status measure, was 49.2 ± 21.9. Hierarchical, multivariable linear regression was used to relate patient characteristics to baseline PAQ. Patient characteristics independently associated with poorer health status were age ( p < 0.001), female sex ( p < 0.001), not being married ( p = 0.02), economic burden (moderate/severe vs none, moderate/severe vs some; p = 0.03), difficulty getting care (moderate/severe vs none, moderate/severe vs some; p < 0.001), chronic lung disease ( p = 0.02), back pain ( p < 0.001), bilateral vs unilateral PAD ( p = 0.02), intermittent claudication severity (moderate vs mild, severe vs mild, p < 0.001), and lack of prior participation in an exercise program ( p = 0.005). Disparities in both vascular and non-vascular factors were associated with patients' health status at the time of presentation and should be addressed by all who care for patients with vascular disease.